PENINGKATAN KECERDASAN BODY KINESTHETIC MELALUI KEGIATAN TARI KREATIF (Penelitian Tindakan di Kelompok B TK/RA Daaruttuqo, Cipondoh) - Rosita Rosita (stit-islamic-village, 2020)
Objectives of the research are to determine the creative dance and to increase body kinesthetic intelligence of children through creative dance. This research was carried out in group B Daaruttuqo kindergarten, Cipondoh Tangerang with 10 subject , on the month from May to June. This research uses an action research design model of Kemmis and Mc Taggart, through two cycles consisting of seven meetings on the first cycle and seven meetings on the second cycle which includes the stages of planning, action, observation and reflection. Data analysis using quantitative and qualitative analysis. Data obtained by referring to the research instrument which refers to the body kinesthetic intelligence. The results showed an increase in body kinesthetic intelligence scores of children with the acquisition of body kinesthetic intelligence classical pre-action reached 37.5%, the first cycle increased the score reached 56.75% and the second cycle was obtained which satisfy the classical score reached 80.75 % so it can be concluded that the activity”creative dance” can improve children's body kinesthetic intelligence.